The Rasulullah's Way of Business: as the Best Example for Student - BADRAH UYUNI (Program Studi Pengembangan Masyarakat Islam STID Mohammad Natsir, 2021)
Doing business is one way to earn sustenance. As in a hadith Rasulullah PBUH states that ninety percent of sustenance lies in business, while the remaining ten percent is livestock. The point is that doing business will open nine doors to get wealth, while another door of sustenance is opened by breeding this shows how important business is in meeting the needs of human life, from the material side. Because ninety percent of the income obtained comes from business. A successful business cannot be separated from several things, one of which must be done based on trust, related to ethics, and related to profit. In practice, doing business according to Islamic law has been carried out by the Prophet Muhammad as a guide for Muslims, so that if a businessman does business according to the teachings of the Prophet, it is the same as carrying out the sunnah of the Prophet Muhammad. More and more entrepreneurs are implementing the behavior of the Prophet in their business, including customer-oriented by maintaining customer satisfaction, openness to customers by applying honest aspects of commerce, conducting healthy competition in the economic market, must pay attention to aspects of justice so that no party is oppressed. Feel disadvantaged when doing business. This study aims to determine the correct implementation of business based on the teachings of the Prophet Muhammad and examine the messages conveyed by the Prophet Muhammad on the aspect of muamalah. This research uses a descriptive qualitative research method with secondary data or library research. Islamic business behavior that is free of usury (interest), gharar (uncertainty), and maysir (gambling) is considered better because of the value requirements. Therefore, extracting the values ​​of Islamic economic philosophy through the business behavior of Muhammad SAW is expected to be a solution for today's business behavior.